Response of Three Sweet Maize Varieties to Leaf Blight (Exserohilum turcicum) Planted in Freshwater Swamps of South Sumatra - Harman Hamidson; Rafika Oktarida (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Planting resistant varieties is the most effective control method and is recommended because it is safe for the environment. The problem to be raised in this study was the use of the same variety of maize in every growing season by farmers. The use of one of these varieties could cause a decrease in yield due to the resistance of the variety to certain pests and diseases. This study aimed to provide information in the form of the use of sweet maize varieties resistant to leaf blight and potential to be planted in the swampy lowland of South Sumatra. The varieties used in this study were Bonanza F1, MB-01 Sweet and Love Sweet varieties. Based on the results of the study, as a whole the use of several varieties had a significant effect on the severity of leaf blight. The results of this study showed that there were differences in the response to resistance of each variety to leaf blight caused by the fungus Exserohilum turcicum. The observation of disease severity was carried out only in the vegetative phase. The highest disease severity was found in the Bonanza, Love Sweet, and MB-01 Sweet varieties at 16.90%, 9.99% and 7.07% respectively. The production data showed that there was no significant effect on the leaf blight. The MB-01 Sweet variety had the potential to be planted on swampy soil because it had resistance to blight and had a high production rate.